Consumer Protection in Modern Transactions: A Review Islamic Criminal Law on Breach of Contract - Ratu Naira Lubis; David Nwanna Dumbiri (AT-TAFAHUM: Journal of Law, 2023)
This study aims to construct a deep understanding of consumer protection in contemporary muamalah practices through the perspective of Islamic criminal law, with a focus on various forms of contractual deviations that have the potential to cause economic and moral losses. The digital transformation in modern economic activities and the increasing complexity of transaction models have opened up space for unlawful acts, such as fraud (tadlis), uncertainty of contractual clauses (gharar), information manipulation, and fraudulent practices (ghabn). In Islamic criminal law, these forms of violations are classified as ta'zir crimes, namely crimes for which the determination of sanctions is left to the competent authorities in order to maintain public order and welfare. This study uses a literature study method by examining primary and secondary sources from Islamic legal thinkers such as Wahbah az-Zuhaili, Abdul Qadir Audah, and Muhammad Abu Zahrah. The results of the analysis show that Islamic criminal law offers a comprehensive normative framework for consumer protection by upholding the principles of justice, transparency of contracts, and prevention of exploitation. The flexibility of the ta'zir concept also provides room for adjusting the types of sanctions to the dynamics of technology and social needs, including in the context of digital transactions. This study concludes that the integration of fiqh muamalah and fiqh jinayah is a relevant approach to strengthen the consumer protection system in the modern era. This framework not only fills the gap in regulations in the categories of hudud and qishas-diyat, but also confirms that Islamic criminal law is normative and adaptive to the development of contemporary economic practices.